The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/medu-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Delayed Presentation at the Dental Clinic of the Federal Medical Centre, Birnin Kebbi, Nigeria

Abstract: Background: It is a very sad experience, as a clinician, to see a patient presenting very late at a dental offi ce with complicated oral health-related problems when the initial causal problem is very cheap, easy, and simple to treat. This study aims to determine the factors causing delay in seeking dental treatment among the patients visiting the dental clinic of the Fedearal Medical Centre, Birnin Kebbi, Kebbi State, Nigeria. Methodology: This study was questionnaire-based survey of 172 non-paediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…in other studies. 14 This, however, contradicts our findings because our study was co nducted in a government setting where the cost of dental treatment is very low or even free but even though most of the patients did mention the cost of delaying their previous dental visits because according to them privates dental treatments costs high and government hospitals in Lakki Marwat do provide patients with very limited treatment facilities and most commonly provided one is tooth extraction. Also, the environment is extremely unhygienic, there is no system for autoclaving and other facilities for an aseptic environment to prevent patients from nosocomial infections.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…in other studies. 14 This, however, contradicts our findings because our study was co nducted in a government setting where the cost of dental treatment is very low or even free but even though most of the patients did mention the cost of delaying their previous dental visits because according to them privates dental treatments costs high and government hospitals in Lakki Marwat do provide patients with very limited treatment facilities and most commonly provided one is tooth extraction. Also, the environment is extremely unhygienic, there is no system for autoclaving and other facilities for an aseptic environment to prevent patients from nosocomial infections.…”
Section: Discussioncontrasting
confidence: 78%
“…The study population consists of females belonging to different socioeconomic statuses but most of them were illiterate and some have very limited education like studies conducted in Nigeria and India. 13,14 Most of the females had made their previous dental visits delayed ultimately, they do report to the OPD with serious dental issues like extreme pain, swelling, severe dental caries, extreme dental plaque, and other esthetic problems. The most reported reasons recorded for delayed dental visits were, Dental disease was not severe which was consistent with findings in a study conducted in India and China.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also supported the hypothesis that the influence of gender, age, SES, and parental education on schoolchildren's dental anxiety is not statistically significant. Although some studies indicated that gender predicts dental anxiety following their report that dental anxiety was higher in adult females than males, 7 12 14 15 16 17 21 one study showed that no gender disparity exists in dental anxiety levels among children. 22 In contrast to some research that found that participants' age was a contributing factor to differences in dental anxiety scores, 7 11 12 15 other studies found the opposite, 8 24 which is consistent with our current findings regarding the relationship between age and dental anxiety in schoolchildren.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of dental anxiety in the current study is comparable to that found in previous studies, which ranged from 7.43 to 62.8%. 7 11 12 13 14 15 16 17 18 19 One study discovered that 47.3% of respondents had low dental anxiety, while 52.7% had high dental anxiety. 20 In another study on dental anxiety, 36.2% of respondents reported being mildly anxious, 57.8% reported being moderately anxious, and 6.0% reported being highly anxious.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study conducted among the patients attending the Department of Dental and Maxillofacial Surgery, Federal Medical Centre, Birnin-Kebbi, Nigeria, from July to October, 2016. This study forms part of the "Dental Health Services Project" conducted in the aforementioned department (Olawole & Kanmodi, 2019).…”
Section: Methodsmentioning
confidence: 99%